Basin-wide contributions to the underwater soundscape by multiple seismic surveys with implications for marine mammals in Baffin Bay, Greenland. (January 2019) - Kyhn, L.A.; Wisniewska, D.M.; Beedholm, K.; Tougaard, J.; Simon, M.; Mosbech, A.; Madsen, P.T.
Abstract: Seismic surveys increasingly operate in deeper Arctic waters with propagation conditions and marine mammal fauna different from the better-studied temperate, or shallow-water, regions. Using 31 calibrated sound recorders, we quantified noise contributions from four concurrent seismic surveys in Baffin Bay, Greenland, to estimate their potential impacts on marine mammals. The impact was cumulative as the noise level rose in response to the onset of each survey: on a minute-by-minute scale the sound-exposure-levels varied by up to 70 dB (20 dB on average), depending on range to the seismic vessel, local bathymetry effects and interference patterns, representing a significant change in the auditory scene for marine mammals. Airgun pulse energy did not decrease to ambient before arrival of the next pulse leaving very little low-frequency masking-free time. Overall, the measured values matched well with pre-season-modeling, emphasizing the importance of noise-modeling in impact assessments, if responses of focal marine mammals are known. Highlights: Activity of four seismic vessels significantly increased ambient noise levels. On a minute-to-minute scale, sound exposure levels varied by 20–70 dB. Ambient noise did not fall to pre-season values throughout the seismic season. The constantly elevated noise level gave little masking-free time over 2.5 months. Measured noise levels were predicted well by pre-season modeling of cumulative effects.